Cerebellar transcriptional alterations with Purkinje cell dysfunction and loss in mice lacking PGC-1α - Lucas, Elizabeth K.; Reid, Courtney S.; McMeekin, Laura J.; Dougherty, Sarah E.; Floyd, Candace L.; Cowell, Rita M. (Frontiers in Cellular Neuroscience, 2015)
Alterations in the expression and activity of the transcriptional coactivator peroxisome proliferator-activated receptor γ coactivator-1α (ppargc1a or PGC-1α) have been reported in multiple movement disorders, yet it is unclear how a lack of PGC-1α impacts transcription and function of the cerebellum, a region with high PGC-1α expression. We show here that mice lacking PGC-1α exhibit ataxia in addition to the previously described deficits in motor coordination. Using q-RT-PCR in cerebellar homogenates from PGC-1α -/- mice, we measured expression of 37 microarray-identified transcripts upregulated by PGC-1α in SH-SY5Y neuroblastoma cells with neuroanatomical overlap with PGC-1α or parvalbumin (PV), a calcium buffer highly expressed by Purkinje cells. We found significant reductions in transcripts with synaptic (complexin1, Cplx1; Pacsin2), structural (neurofilament heavy chain, Nefh), and metabolic (isocitrate dehydrogenase 3a, Idh3a; neutral cholesterol ester hydrolase 1, Nceh1; pyruvate dehydrogenase alpha 1, Pdha1; phytanoyl-CoA hydroxylase, Phyh; ubiquinol-cytochrome c reductase, Rieske iron-sulfur polypeptide 1, Uqcrfs1) functions. Using conditional deletion of PGC-1α in PV-positive neurons, we determined that 50% of PGC-1α expression and a reduction in a subset of these transcripts could be explained by its concentration in PV-positive neuronal populations in the cerbellum. To determine whether there were functional consequences associated with these changes, we conducted stereological counts and spike rate analysis in Purkinje cells, a cell type rich in PV, from PGC-1α -/- mice. We observed a significant loss of Purkinje cells by six weeks of age, and the remaining Purkinje cells exhibited a 50% reduction in spike rate. Together, these data highlight the complexity of PGC-1α’s actions in the central nervous system and suggest that dysfunction in multiple cell types contribute to motor deficits in the context of PGC-1α deficiency.